Analisis anggaran operasional sebagai alat pengendalian keuangan pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Banggai Kepulauan - Tukunan, Stela Viviana; Elim, Inggriani; Kindangen , Wulan D. (Yayasan Widyantara Nawasena Raharja, 2024)
Operational budget serves as a tool for companies to achieve profit or income objectives. Financial control remains a critical concern for both profit-oriented and non-profit organizations. This research aims to analyze and comprehend the realization of operational budgets as a financial control instrument within the context of the Regional Drinking Water Company (PDAM) in Banggai Kepulauan Regency. The data analysis method employed is qualitative descriptive analysis, utilizing data collection techniques including observation, interviews, and documentation. The study delves into the comparison between operational budgets and the actual operational costs realized by PDAM Banggai Kepulauan Regency from 2019 to 2021. Across this period, fluctuations are observed in the percentages of operational budgets that have been realized. In 2019, the actual cost realization reaches 110% of the budget with a 10% variance. Similarly, in 2020, the actual cost realization amounts to 116% of the budget with a 16% variance, and in 2021, the actual cost realization reaches 121% of the budget with a 21% variance. The analysis findings highlight that the most significant cost component is transmission and distribution expenses, consistently exhibiting a high percentage of realization, averaging 130% of the budget. The primary cause of this variance is attributed to the unallocated depreciation costs for transmission and distribution installations, which were absent from the operational plan. Throughout the 2019-2021 period, PDAM Banggai Kepulauan experienced incongruities between budgeted and realized costs, particularly concerning transmission and distribution expenses, resulting in adverse financial impacts.